Definiowanie tożsamości regionalnej społeczności Warmii i Mazur w formule radiowych pejzaży dźwiękowych kultur pamięci - Szydłowska, Magdalena (Zagadnienia Rodzajów Literackich, 2021)
Soundscape is a natural acoustic environment of man. Its elements are various constructions, listening impressions, recordings, programmes. While exploring this space, the researcher encounters many interesting aspects related to the contemporary perception of completed events in the form of auditive memory cultures. It can be saved and placed in the media. For example on Radio Olsztyn a public broadcaster from Warmia and Mazury in Poland. Therefore, it is possible to carry out research of the auditive cultural memory based on the radio programmes and their problematic issues. This specific, evolving cultural area of the region is worthy of analysis.